BIOPHYSICS AND MEDICINE: THE MEETING POINT OF MODERN SCIENCES (The New Uzbekistan Journal of Medicine, 2025)
This article covers the content of biophysics, its role and significance in medicine. The importance of biophysics in diagnostic, treatment and prevention processes, as well as its inextricable link with modern medical technologies, is analyzed. The branches of the field of biophysics are currently achieving many achievements in many areas, especially in the field of medicine. The principles of biophysics are the basis of modern medicine. The development of biophysics is directly related to the development of medical fields, in fact, most modern medical devices are based on the laws of physics and work with physical instruments and the laws of physics.